Compensation and Productive Efficiency in Partnerships: Evidence from Medical Groups Practice - Gaynor, Martin; Pauly, Mark V. (Journal of Political Economy, 1990)
Relatively little is known about the behavior and performance of firms organized as partnerships. In this paper we attempt to fill that gap by developing and testing a model of the effect of alternative compensation arrangements on productive efficiency in medical group practices. The technique employed is maximum likelihood production frontier estimation. We provide a simple behavioral model of the determination of productive efficiency and a new interpretation of the economic measure of technical efficiency. We derive a "behavioral production function" that relates production to individual responses to incentives, and we indicate the impossibility of recovering the parameters of the production technology from observed behavior. Overall, the empirical results indicate that incentives do affect productivity. A larger number of members in a group decreases productivity while greater average experience leads to greater productivity.